Information literacy for the digital age - Atanda, Balogun Naeem (Ilorin Press, 2019)
The idea of Information Literacy began many decades ago in libraries under the label of 'library literacy', when public and academic libraries were foremost places or institutions where people could search through large collections of printed documents for the factual, fictional, educational or entertainment information they need. The computer revolution that began about the 1950s has since brought great transformations of societies into being technology driven. It has brought to limelight the importance of various other types of literacies, including information literacy, technology literacy, and digital literacy. Information literacy is nowadays defined much more broadly than library literacy to include knowledge and skills in knowing what information to search to solve various problems, where to search for needed information (which nowadays include library, non-library, printed and online sources), how to evaluate and use the information to solve problems, how to ensure compliance with ethical and legal requirements of information access and use, how to use digital technologies to search, evaluate, use, and communicate the information, and so on. Hence, this book and the range of topics covered in its thirteen chapters.